2021
DOI: 10.3390/antibiotics10080918
|View full text |Cite
|
Sign up to set email alerts
|

Medical-Grade Honey as an Alternative Treatment for Antibiotics in Non-Healing Wounds—A Prospective Case Series

Abstract: Non-healing wounds are usually colonised by various types of bacteria. An alternative to antibiotic treatment in patients with infected wounds with local signs of inflammation may be medical-grade honey (MGH), which favourably affects the healing process with its antimicrobial, antioxidant, anti-inflammatory, and immunomodulatory properties. The objective of this study was to evaluate the effect of MGH therapy on the healing process of non-healing wounds of various aetiologies and different wound colonisations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 41 publications
4
19
0
Order By: Relevance
“…Its wound healing properties are orchestrated by multiple mechanisms. It creates a moist wound environment, promotes autolytic debridement, angiogenesis, and re-epithelialization, and reduces oxidative and inflammatory stress [31,41,[43][44][45][46]. Moreover, MGH has previously been shown to have anti-inflammatory activity, which is in line with the reduced pain and itching in the current study [41,43].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Its wound healing properties are orchestrated by multiple mechanisms. It creates a moist wound environment, promotes autolytic debridement, angiogenesis, and re-epithelialization, and reduces oxidative and inflammatory stress [31,41,[43][44][45][46]. Moreover, MGH has previously been shown to have anti-inflammatory activity, which is in line with the reduced pain and itching in the current study [41,43].…”
Section: Discussionsupporting
confidence: 78%
“…Since both honey and vitamins C and E have been shown to possess antiviral activity [36][37][38][39][40], they may also help to treat cold sores. The wound healing activities of MGH are also based on multiple mechanisms, and therefore may further advance the healing of the cold sores [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…MGH also demonstrated a synergistic activity with the other ingredients of L-Mesitran Soft on the inhibition and eradication of biofilms [104]. Moreover, L-Mesitran Soft is effective in treating chronic wounds infected with (multi-resistant) bacteria, even when present in biofilms [65,104,111]. There is extensive evidence of the antimicrobial and wound healing properties of L-Mesitran Soft in literature, and no negative side effects or safety issues have been reported [65,[68][69][70][71]104,111,112].…”
Section: Rationale For Selecting the Mgh-based Formulationmentioning
confidence: 96%
“…Moreover, L-Mesitran Soft is effective in treating chronic wounds infected with (multi-resistant) bacteria, even when present in biofilms [65,104,111]. There is extensive evidence of the antimicrobial and wound healing properties of L-Mesitran Soft in literature, and no negative side effects or safety issues have been reported [65,[68][69][70][71]104,111,112]. This should ease the registration of the product for new indications, such as RVVC, when the trial is successful.…”
Section: Rationale For Selecting the Mgh-based Formulationmentioning
confidence: 99%
“…A recent in vivo study has shown an interesting positive impact upon the healing process of chronic wounds when treated with medical-grade honey (MGH) while the absence of any antibiotic drugs in almost all patients (eight of nine cases) [26]. This is because wound odor, pain, exudation, and signs of wound infections were completely inattentive following the application of the MGH.…”
Section: Review Honey As a Wound Remedymentioning
confidence: 99%